anonymous
  • anonymous
solve the quadratic equation by completing square x^2 +8x =7 a. x=-1 +/- sqrt23 b. x=4+sqrt23 c. x=-4+/- 2 sqrt23 d. x=-4+/-sqrt23 a. z=-8+/-sqrt17 b. z=8+sqrt17 c. z= -16 +sqrt47 d. z=8 +/- sqrt47
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
b=8 so... (8/2)^2 = 4^2 = 16 so add that to both sides so x^2 + 8x + 16 = 7 + 16 so now you have x^2 + 8x + 16 = 23 so FOIL the left side and you get (x + 4)(x + 4) = 23 or (x + 4)^2 = 23 so x + 4 = sq. root 23 so x = -4 + sq. root 23
anonymous
  • anonymous
if you dont mind me asking how is it you got the sixteen? you multiplied by two i beleive how is it you got that number?
anonymous
  • anonymous
ok so the coefficient of x is 8 right? your original equation is x^2 + 8x = 7, so the standard form for that equation is ax^2 + bx + c = 0 well in this particular equation there is no c cuz c has already been put over on the right side of the equation, and a=1 since there's nothing in front of x^2...and there's an 8 in front of x so b=8. so you take half of whatever b is and then square that number....so since b=8 you take (8/2) which is 4 and then square it so 4^2 = 16 now add that number (16) to both sides of your original equation so x^2 + 8x + 16 = 7 + 16 so x^2 + 8x + 16 = 23 understand?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
yes thanks a bunch
anonymous
  • anonymous
bovice?

Looking for something else?

Not the answer you are looking for? Search for more explanations.